2016
DOI: 10.1016/j.cell.2016.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Corpse Engulfment Generates a Molecular Memory that Primes the Macrophage Inflammatory Response

Abstract: SummaryMacrophages are multifunctional cells that perform diverse roles in health and disease. Emerging evidence has suggested that these innate immune cells might also be capable of developing immunological memory, a trait previously associated with the adaptive system alone. While recent studies have focused on the dramatic macrophage reprogramming that follows infection and protects against secondary microbial attack, can macrophages also develop memory in response to other cues? Here, we show that apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
204
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(217 citation statements)
references
References 64 publications
(90 reference statements)
8
204
0
Order By: Relevance
“…A possible explanation for this discrepancy would be that hemocytes may differ in their expression profile, behavior, and phagocytic ability at various developmental stages due to differences in their microenvironment and/or sensitivity to stimuli. Accordingly, it has recently been shown that the phagocytic activity of embryonic hemocytes acts as a priming mechanism, increasing the ability of primed cells to phagocytose bacteria at later stages [78]. It is therefore possible that embryonic, larval and adult hemocytes display very different levels of priming and bacterial phagocytic activity, and that crq is required mostly in larval/adult bacterial phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this discrepancy would be that hemocytes may differ in their expression profile, behavior, and phagocytic ability at various developmental stages due to differences in their microenvironment and/or sensitivity to stimuli. Accordingly, it has recently been shown that the phagocytic activity of embryonic hemocytes acts as a priming mechanism, increasing the ability of primed cells to phagocytose bacteria at later stages [78]. It is therefore possible that embryonic, larval and adult hemocytes display very different levels of priming and bacterial phagocytic activity, and that crq is required mostly in larval/adult bacterial phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The process of macrophage “priming” or “training” occurs when prior exposure to a specific stimulus induces an enhanced immune response, such as increased microbicidal activity (i.e., increased phagocytic activity and increased expression of pro-inflammatory genes) [58]. As examples, stimuli that trigger priming can include phagocytosis of apoptotic cells [59], ingestion of ß-glucan (present in the Candida cell wall) [60], or exposure to lipopolysaccharide (LPS) [61]. In addition to altering gene expression, these stimuli can induce changes in metabolic function, such as triggering macrophages to switch to glucose metabolism to increase energy production for supporting increased cellular activation [62].…”
Section: Text Of the Reviewmentioning
confidence: 99%
“…Our data indicates that K63-polyubiquitylation on phagosomal 340 proteins is also used as a scaffold for the recruitment of signalling complexes, in particular the kinase complex TAK1/MKK7/JNK to MSR1 via specific polyubiquitylation on a conserved lysine K27. Remarkably, we could show that only MKK7 and not MKK4 2018; tissue damage and that this priming and subsequent recruitment to wounds was dependent on JNK (Weavers et al, 2016). This suggests that JNK activation induced by uptake of apoptotic bodies could regulate various responses.…”
Section: Ligases (Bilkei-gorzo Et Al Unpublished Data)mentioning
confidence: 54%